(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The paper is an attempt to summarize 25 years of experience of Furniture Design Education at the University of Forestry. The author attempts to look at the whole complex circle of problems facing the management and teaching staff at the university, such as compiling of curriculum and syllabi, creating study content and textbooks, securing study space and all organizational issues. On the non–material side key issues were: awareness of the creative nature of the designer’s profession; establishing of artistic ethos and new relationship between staff and students; innovative teaching methods encouraging self-confidence and presentational skills of young people. These issues include not only staff and facilities, but also active involvement of students. Here we mean active student participation in: mobility programs abroad, national and international workshops, annual exhibitions, introducing opportunities for professional career at the university. In this line we can add the educational module “Project Week” and links with business. Meanwhile, positive program accreditation of the Engineering Design Program by the National Accreditation Agency; as well as the image of our alumni and their overall professional career gave the first rewarding signs. Last but not least, the report compares the program with analogical programs elsewhere in Europe with consequent conclusions for success and failures.